2019
DOI: 10.1111/his.13846
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological factors associated with BRAF‐V600E mutation in colorectal serrated adenomas

Abstract: Serrated adenomas are genetically heterogeneous, and the histological classification into sessile serrated (SSA) adenoma and traditional serrated adenoma (TSA) does not reflect the molecular landscape. The objective of this study was to assess clinical or pathological factors associated with BRAF‐V600E mutation in serrated adenomas. Systematic review and meta‐analysis was performed by searching electronic databases from January 2011 to January 2019 for studies assessing the association of BRAF‐V600E mutation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…The role of MUC6 was evaluated in SSA/Ps lesions and is controversial [84]. Nevertheless, MUC6 was assessed to be a supportive immunohistochemical marker to differentiate SSA/Ps from TSAs [97,98].…”
Section: Molecular Features Of the Serrated Colorectal Precursor Lmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of MUC6 was evaluated in SSA/Ps lesions and is controversial [84]. Nevertheless, MUC6 was assessed to be a supportive immunohistochemical marker to differentiate SSA/Ps from TSAs [97,98].…”
Section: Molecular Features Of the Serrated Colorectal Precursor Lmentioning
confidence: 99%
“…The clinical role of MSI and CIMP has not been precisely described as opposed to BRAF and KRAS mutations. In general, BRAF mutated, MSI and CIMP CRCs are more frequent in females and often localized in the proximal colon [98,161]. MSI CRCs present a good prognosis, while BRAF mutated and CIMP tumors are related to a later age-of-onset and to a poor clinical outcome [38,65].…”
Section: Clinical Relevance Of Molecular Alterations In the Serratmentioning
confidence: 99%
“…20,25 BRAF mutations appear to be particularly common in proximal TSAs < 10 mm in size. 21 This genetic profile is the same as that of microvesicular HPs and SSLs, suggesting that proximally located TSAs may develop from one of these precursor lesions. A third, smaller group of TSAs have been identified that harbour neither BRAF nor KRAS mutations.…”
Section: G O B L E T C E L L -R I C H H P S a N D T S A Smentioning
confidence: 68%
“…20 Microvesicular HPs and left-sided SSLs show only low-level to intermediatelevel genomic methylation, whereas right-sided SSLs show high-level methylation. 20,21 CRC developing along this pathway also shows BRAF V600E mutation, and this is associated with high-level genomic methylation [CpG island methylator phenotype (CIMP)-high status], resulting in inactivation of certain genes. In particular, methylation of the promoter sequence for MLH1 leads to inactivation of this gene and therefore to loss of expression of MLH1 (and its partner molecule PMS2) and microsatellite instability (MSI) in areas of dysplasia (dysplasia NOS and minimal deviation dysplasia) arising in SSLs and associated CRCs.…”
Section: I C R O V E S I C U L a R H P S A N D S S L Smentioning
confidence: 99%
“…Sessile serrated adenomas have a higher risk of developing into malignant tumors because of their special biologic behavior, so they should be paid more attention. 8,9…”
Section: Risk Factors For Early and Late Adenoma Recurrence With Regamentioning
confidence: 99%